The wHole Story About Fenestrations in LSEC - Szafranska, Karolina; Kruse, Larissa D.; Holte, Christopher Florian; McCourt, Peter; Zapotoczny, Bartlomiej (Frontiers in Physiology, 2021)
The porosity of liver sinusoidal endothelial cells (LSEC) ensures bidirectional passive transport of lipoproteins, drugs and solutes between the liver capillaries and the liver parenchyma. This porosity is realized via fenestrations – transcellular pores with diameters in the range of 50-300 nm – typically grouped together in sieve plates. Aging and several liver disorders severely reduce LSEC porosity, decreasing their filtration properties. Over the years, a variety of drugs, stimulants and toxins have been investigated in the context of altered diameter or frequency of fenestrations. In fact, any change in the porosity, connected with the change in number and/or size of fenestrations is reflected in the overall liver-vascular system crosstalk. Recently, several commonly used medicines have been proposed to have a beneficial effect on LSEC re-fenestration in aging. These findings may be important for the aging populations of the world. In this review we collate the literature on medicines, recreational drugs, hormones and laboratory tools (including toxins) where the effect LSEC morphology was quantitatively analyzed. Moreover, different experimental models of liver pathology are discussed in the context of fenestrations. The second part of this review covers the cellular mechanisms of action to enable physicians and researchers to predict the effect of newly developed drugs on LSEC porosity. To achieve this, we discuss four existing hypotheses of regulation of fenestrations. Finally, we provide a summary of the cellular mechanisms which are demonstrated to tune the porosity of LSEC.